Effects of chiral helimagnets on vortex states in a superconductor. (13th October 2016) - Fukui, Saoto; Kato, Masaru; Togawa, Yoshihiko
Abstract: We have investigated vortex states in chiral helimagnet/superconductor bilayer systems under an applied external magnetic field H appl, using the Ginzburg–Landau equations. Effect of the chiral helimagnet on the superconductor is taken as a magnetic field H CHM, which is perpendicular to the superconductor and oscillates spatially. For H appl = 0 and weak H CHM, there appear pairs of up- and down-vortices. Increasing H appl, down-vortices gradually disappear, and the number of up-vortices increases in the large magnetic field region. Then, up-vortices form parallel, triangular, or square structures.